Initial Public Offerings: An Analysis of Theory and Practice - BRAU, JAMES C.; FAWCETT, STANLEY E. (Journal of Finance, 2006)
ABSTRACT We survey 336 chief financial officers (CFOs) to compare practice to theory in the areas of initial public offering (IPO) motivation, timing, underwriter selection, underpricing, signaling, and the decision to remain private. We find the primary motivation for going public is to facilitate acquisitions. CFOs base IPO timing on overall market conditions, are well informed regarding expected underpricing, and feel underpricing compensates investors for taking risk. The most important positive signal is past historical earnings, followed by underwriter certification. CFOs have divergent opinions about the IPO process depending on firm‐specific characteristics. Finally, we find the main reason for remaining private is to preserve decision‐making control and ownership.